How to buy real estate overseas - Peddicord, Kathleen (Wiley, 2013)
Practical advice on how to enjoy the unique benefits and avoid the pitfalls of investing in real estate abroad In the current uncertain investment climate, foreign real estate represents a more important opportunity than ever before, for both the investor who wants to move a portion of their wealth abroad and the retiree looking for affordable living options. How to Buy Real Estate Overseas explains one of the best options available today for diversification, asset protection, and a safe haven for wealth. Foreign property is a hard asset that, unlike stocks, for example, can't go bankrupt and collapse to zero. This book is an expert guide to the advantages and the challenges of investing in real estate overseas. Author Kathleen Peddicord, an American currently based in Panama, is considered the world's foremost authority on overseas retirement and foreign property investment. She has traveled to more than 50 countries, invested in real estate in 18, established businesses in 7, renovated historic properties in 6, and educated her children in 4. She knows from personal experience how foreign real estate can appreciate significantly over time, throw off an annual cash flow, and provide personal enjoyment for you and your family. An investment in a piece of real estate in a foreign country is a chance for both profit and fun. How to Buy Real Estate Overseas offers practical advice on how to find great deals, buy and manage property profitably in unfamiliar and potentially volatile foreign markets.